Leadership views on corporate chaplains: business, sociocultural, and spiritual justifications - Miller, David W. (Journal of management, spirituality & religion, 2015)
Spirituality in the workplace continues to garner growing scholarly and popular attention as evidenced by increased interdisciplinary scholarship, media reports, corporate interest, and employee activity. Workplace chaplaincy, an expression of the faith at work movement has received attention from media and practitioners; however, there remains a dearth of scholarly research. This paper, part of a wider study on workplace chaplaincy, fills that scholarly void by explicating the business reasoning, sociocultural explanations, and spiritual imperatives behind organizational leaders' decisions to incorporate workplace chaplains into their employee benefit programs. Through interviews with CEOs and C-Suite leaders, this study found that workplace chaplains offer a unique kind of care for employees' otherwise unmet in other benefit programs, and appears to contribute positively to organizational commitment, employee well-being, reduced operational costs, reduced turnover/increased retention, and an overall positive, welcoming organizational culture. The paper ends with implications for future studies in areas such as; potential challenges associated with corporate chaplaincy, perceptions of employees and other constituents, and metrics for evaluating chaplaincy programs.